(untitled) (Práxis Educativa, 2022)
This article is based on a Doctoral research, focused on the evaluation of pedagogical practices awarded by the 4th Educar para a Igualdade Racial (Educate for Racial Equality) Award, conceived by the Center for Studies on Work Relations and Inequalities. The goal is to analyze the pedagogical practices carried out by the teachers who won the 4th edition of this Award, in order to demonstrate elements present in the elaboration of pedagogical actions in face of the complexity of racism in the Brazilian society. To do so, it is demonstrated the trajectory of the Black Educator Movement in the creation of Law no. 10.639/2003, as well as it is discussed its unfoldings and challenges from the perspective of emancipatory education. Finally, it is pointed out relevant elements for the anti-racist fight in the school context. Keywords: Racism. Educate for Racial Equality Award. Confrontation. School.